Transformasi Pendidikan: Bagaimana Kepuasan Kerja dan Kepemimpinan Mendorong Inovasi Guru? - Aisya Dwi Rohmawati; Diah Sofiah; Hikmah Husniyah Farhanindya (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2026)
Educational transformation requires teachers who demonstrate proactive behavior in supporting change and innovation in schools. This study aims to determine the role of job satisfaction and transformational leadership on change-oriented organizational citizenship behavior among teachers. The study employed a quantitative approach with correlational design involving 105 public junior high school teachers selected using census method. Data collection used Change-Oriented Organizational Citizenship Behavior Scale, Job Satisfaction Scale, and Perceived Transformational Leadership Scale. Data were analyzed using multiple regression. Results showed that job satisfaction and transformational leadership together significantly predict change-oriented organizational citizenship behavior. Partially, job satisfaction proved to be highly significant positive predictor, while transformational leadership had no significant effect. Job satisfaction is key factor in encouraging teachers' proactive behavior to support educational transformation. Keywords: Change-oriented organizational citizenship behavior; job satisfaction; proactive behavior; teachers; transformational leadership Transformasi pendidikan membutuhkan guru yang menampilkan perilaku proaktif dalam mendukung perubahan dan inovasi di sekolah. Penelitian ini bertujuan mengetahui peran kepuasan kerja dan kepemimpinan transformasional terhadap change-oriented organizational citizenship behavior pada guru. Penelitian menggunakan pendekatan kuantitatif dengan desain korelasional melibatkan 105 guru sekolah menengah pertama negeri yang dipilih dengan metode sensus. Pengumpulan data menggunakan Skala Change-Oriented Organizational Citizenship Behavior, Skala Kepuasan Kerja, dan Skala Persepsi Kepemimpinan Transformasional. Data dianalisis menggunakan regresi berganda. Hasil menunjukkan kepuasan kerja dan kepemimpinan transformasional secara bersama-sama memprediksi change-oriented organizational citizenship behavior secara signifikan. Secara parsial, kepuasan kerja terbukti menjadi prediktor positif yang sangat signifikan, sedangkan kepemimpinan transformasional tidak berpengaruh signifikan. Kepuasan kerja merupakan faktor kunci dalam mendorong perilaku proaktif guru untuk mendukung transformasi pendidikan. Kata kunci: change-oriented organizational citizenship behavior; guru; kepemimpinan transformasional; kepuasan kerja; perilaku proaktif